2021
DOI: 10.21203/rs.3.rs-516363/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Knowledge, Attitudes and Practices of Malaria Among Forest-Goer Communities in Mukdahan Province, Northeastern Thailand

Abstract: Background: Malaria remains a major public health challenge in Thailand. In Thailand, the transmission now progressively clusters in hotspots along international borders and among high-risk groups, including forest-goers. Therefore, continuous assessment and understanding of the behavioral and perceptions related to malaria exposure in the high-risk group are necessary to achieve the elimination goal. This study aimed to investigate knowledge, attitudes and practices (KAP) related to malaria in rural communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Similar findings were found in this study that forest goers and their family members' choice of providers were determined by socio-economic status and having more providers in their village [15,16,30,31,41,42,[48][49][50]. In cases of knowledge of malaria prevention and transmission, almost all of the forest goers in a Thailand study were aware that malaria was transmitted by mosquitoes and bed nets were used to prevent malaria [32]. Similarly, it was found that forest-goers in GMS countries often had knowledge of malaria transmission [20].…”
Section: Characteristicsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar findings were found in this study that forest goers and their family members' choice of providers were determined by socio-economic status and having more providers in their village [15,16,30,31,41,42,[48][49][50]. In cases of knowledge of malaria prevention and transmission, almost all of the forest goers in a Thailand study were aware that malaria was transmitted by mosquitoes and bed nets were used to prevent malaria [32]. Similarly, it was found that forest-goers in GMS countries often had knowledge of malaria transmission [20].…”
Section: Characteristicsupporting
confidence: 74%
“…In addition, their socio-economic status seemed to influence their health-seeking behaviour from providers. Self-medication and home treatment were found to be common in these populations [30][31][32]. Age was found to be a predictor for providers' choice and the association was mixed for different occasions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many respondents considered VMWs or MPWs as essential primary care providers for malaria. Like elsewhere in the GMS (Cambodia [ 27 , 42 45 ], Lao PDR [ 46 ], Myanmar [ 47 ], and Vietnam [ 48 ]), village residents in Thailand are likely to seek testing and treatment from local health workers [ 49 , 50 ]. Nevertheless, their decision to seek treatment at a malaria clinic or hospital in the district depended less on its distance from home than in other countries, likely because of better access to care compared to other communities in mountainous and remote areas, particularly in the rainy season, or the perceived cost of treatment elsewhere [ 51 ].…”
Section: Discussionmentioning
confidence: 99%